2021
DOI: 10.1093/neuonc/noab090.211
|View full text |Cite
|
Sign up to set email alerts
|

Epct-25. Smo Protein Depletion in SHH Medulloblastomas Using Microbubble-Enhanced Ultrasound and Sirna Loaded Cationic Nanoparticles

Abstract: RNA-based therapies offer unique advantages for treating pediatric brain tumors. However, the systemic delivery remains a major problem due to degradation of unmodified RNA in biological fluids, poor brain accumulation, and poor cancer cell uptake or escape from the endosomal lipid bilayer barrier. While nanoparticle encapsulation can prolong circulation time and facilitate cellular uptake, their accumulation in brain tumor remains particularly poor due to their low permeability across the blood-brain barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In pediatric and adult preclinical brain tumor models, delivery of siRNA with 50 nm cationic lipid-polymer hybrid nanoparticles (LPHs:siRNA), combined with microbubble (MB) enhanced focused ultrasound (MB-FUS) resulted in siRNA delivery with more than 10 times improvement into brain tumor microenvironments and remarkably improved survival benefits. 143 In another example, Lopez-Bertoni, Hernando et al (2018) showed that the development of miRNA-containing polymeric nanoparticles exhibits enhanced crossing of the BBB and shows the inhibition effect on the tumor. Furthermore, in vivo co-delivery of both miR-148a and miR-296-5p as multiplexed nano-miRs inhibited the growth of established orthotopic human GBM xenografts in a mouse model, and reduced tumor burden more significantly compared to miRNA delivered alone.…”
Section: Nanomedicines In Brain Tumor Treatmentmentioning
confidence: 99%
“…In pediatric and adult preclinical brain tumor models, delivery of siRNA with 50 nm cationic lipid-polymer hybrid nanoparticles (LPHs:siRNA), combined with microbubble (MB) enhanced focused ultrasound (MB-FUS) resulted in siRNA delivery with more than 10 times improvement into brain tumor microenvironments and remarkably improved survival benefits. 143 In another example, Lopez-Bertoni, Hernando et al (2018) showed that the development of miRNA-containing polymeric nanoparticles exhibits enhanced crossing of the BBB and shows the inhibition effect on the tumor. Furthermore, in vivo co-delivery of both miR-148a and miR-296-5p as multiplexed nano-miRs inhibited the growth of established orthotopic human GBM xenografts in a mouse model, and reduced tumor burden more significantly compared to miRNA delivered alone.…”
Section: Nanomedicines In Brain Tumor Treatmentmentioning
confidence: 99%